2008
DOI: 10.1002/iub.106
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte programmed cell death

Abstract: SummaryEryptosis, the suicidal death of erythrocytes, is characterised by cell shrinkage, membrane blebbing and cell membrane phospholipid scrambling with phosphatidylserine exposure at the cell surface. Phosphatidylserine-exposing erythrocytes are recognised by macrophages, which engulf and degrade the affected cells. Reported triggers of eryptosis include osmotic shock, oxidative stress, energy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
262
1
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 253 publications
(272 citation statements)
references
References 137 publications
(72 reference statements)
5
262
1
4
Order By: Relevance
“…Moreover, the degradation of erythrocytes involves a characteristic pathway called eryptosis, which is a version of apoptosis. These cells lack both nucleus and mitochondria, but PS externalization is also characteristic for them (Foller et al 2008).…”
Section: Aminophospholipid Asymmetry Of Plasma Membrane and Its Apoptmentioning
confidence: 99%
“…Moreover, the degradation of erythrocytes involves a characteristic pathway called eryptosis, which is a version of apoptosis. These cells lack both nucleus and mitochondria, but PS externalization is also characteristic for them (Foller et al 2008).…”
Section: Aminophospholipid Asymmetry Of Plasma Membrane and Its Apoptmentioning
confidence: 99%
“…Many cells exhibit transient exoplasmic protrusions, known as blebs, during several physiological processes, including cytokinesis, cell motility, apoptosis, and virus uptake [3][4][5][6][7][8][9]. Recent experiments revealed that blebs can be induced in suspended fibroblasts when these are subjected to a localized ablation of the cortical CSK [10].…”
Section: Introductionmentioning
confidence: 99%
“…Beyond Gardos channel activation and cell shrinkage, an increase in free [Ca 2+ ] i could also lead to scramblase activation and phosphatidylserine exposure on the outer membrane leaflet. Cation channels are thus implicated in the cascade of events leading to RBCs death, a phenomenon called eryptosis (as an erythrocytic-specific apoptosis) and described by the group of Florian Lang (Foller et al, 2008a;F. Lang et al, 2006;K.S.…”
Section: Non-selective Cation Channelmentioning
confidence: 99%
“…This follows the same path: an external signal (oxidative stress, for example) triggers a rise in intracellular Ca 2+ , probably by activation of a non-selective cation channel by prostaglandin E2. This provokes cell shrinkage, scramblase and calpain activation resulting in phosphatidylserine exposure and degradation of the cytoskeleton (reviewed in (Foller et al, 2008a;F. Lang et al, 2006)).…”
Section: Senescencementioning
confidence: 99%